2018
DOI: 10.31234/osf.io/w48cd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teleological Explanation and Positive Emotion Serially Mediate the Effect of Religion on Well-Being

Abstract: Objective: Previous research has demonstrated a robust relationship between religiosity and well-being, and it has been proposed that positive emotions are important mediators of this effect. Yet the mechanism via which religiosity promotes positive emotions has not been widely studied. We sought to examine whether teleological explanations of daily events and resulting positive emotions serially mediated the effects of religiosity on well-being.Method: These hypotheses were tested over three studies. In study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
0
6
0
1
Order By: Relevance
“…In China, Buddhist symbols and religiosity are associated with increased life satisfaction and happiness [22]. In Singapore, religiosity (among Christians, Buddhists and Muslims) is associated with positive emotions and well-being [23]. In addition, beliefs and techniques derived from East Asian religions are used in various health-related domains such as counseling, psychotherapy, or clinical psychology [24].…”
Section: Health and Well-beingmentioning
confidence: 99%
“…In China, Buddhist symbols and religiosity are associated with increased life satisfaction and happiness [22]. In Singapore, religiosity (among Christians, Buddhists and Muslims) is associated with positive emotions and well-being [23]. In addition, beliefs and techniques derived from East Asian religions are used in various health-related domains such as counseling, psychotherapy, or clinical psychology [24].…”
Section: Health and Well-beingmentioning
confidence: 99%
“…The role of religious beliefs and observances has a positive effect on an individual's well-being and life satisfaction despite life's setbacks, negative circumstances, or uncertainties (Abu-Raiya et al, 2015;Krause, 2015;Koenig & Larson, 2001). Having strong faith convictions and religious involvement may decrease cognitive dissonance (Kitchens & Phillips, 2018), maintain positive appraisal of one's life (Vishkin et al, 2016;Ramsay, Tong, Chowdhury, & Ho, 2019), and strengthen the level of well-being (Galen & Kloet, 2011). In addition, faithful adherence to Church teachings and practices, membership in church organization, and participation in the mass contributed to higher spiritual well-being (Oracion & Madrigal, 2019).…”
Section: Relationship Between Religiosity and Spiritual Well-beingmentioning
confidence: 99%
“…Adults not only apply teleological thinking to their significant life events, but also to less momentous but still relevant moments in their lives. Ramsay et al (2019) found that adults in Singapore regularly explain ostensibly unremarkable events, such as receiving a small, unexpected gift, spending time with a family member they had not seen in a while, or a fun discussion about hobbies with a work colleague, in teleological terms. More religious adults gave more teleological explanations.…”
Section: Naturalizing God-consciousnessmentioning
confidence: 99%